(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
The purpose of the study is to study the physical development and morbidity of preschool children and to conduct a hygienic assessment. Research materials and methods: 502 children educated in a preschool educational institution underwent a medical examination, and a hygienic assessment of their physical development was performed using the generally accepted method. Results: The results of a comprehensive assessment of physical development showed that 76% of children had an average level of physical development, 8% had above-average physical development, 2% had high physical development, 8% had below-average physical development, and 6% had very low physical development. 82% of children had harmonious physical development, and up to 28% had certain changes in somatometric indicators. The results of the assessment of children’s health indicators showed that 83% of preschool children needed to be healthy.